Pattern and outcome of electrolytes imbalance in acute stroke patients admitted in a tertiary care hospital in Khulna city - Kabir, Muhammad Ashraful; Islam, Baishakhi; Rahman, Tasnim; Ghosh, Kakali Rani (Mediscope, 2022)
Stroke is a major public health problem and a leading cause of chronic disability and death. There is scarcity of data about electrolytic disturbances in acute stroke, especially in developing countries. The objective of this study is to find out electrolyte disturbances among acute stroke patients and their association with severity of acute stroke and outcome. It was a cross-sectional study, conducted over a period of one year from 01/06/2018 to 31/05/2019, on 80 selected clinically and CT scan proven acute stroke patients at Gazi Medical College Hospital, Khulna. Out of 80 patients, 50 (62.5%) were male and 30 (37.5%) were female. Majority of the patients (38.7%) were above 70 years age group. CT scan findings revealed, 16 (20%) haemorrhagic, 60 (75%) ischaemic and 4 (05%) mixed (both haemorrhagic and ischaemic) stroke. Seventy-two (90%) of patients had unilateral and only 8 (10%) had bilateral lesion. Dyselectrolytemia was evident in 65% of total stroke patients. Thirty-five percent of all patients had hypokalaemia which was the most common dyselectrolytemia. Out of 20 patients with hyponatremia, 14 died and out of 28 patients with hypokalaemia, 14 died. Out of total 80 patients 48 (60%) had improved and 4 (5%) had been unchanged and referred to higher centre. Mediscope 2022;9(1): 20-24